Apert Syndrome (Bangladesh Medical Journal Khulna, 2012)
Apert syndrome is a rare autosomal dominant malformation. In the recent past we encountered a boy of 16 months with fusion of both fingers and toes, dysmorphic facial features presenting with cough and respiratory distress in Khulna Medical College hospital. Considering the general paucity of cases of acrocephalosyndactyly in the Bangladeshi literature, this case demands reporting. Careful evaluation is necessary in a doubtful case to optimize the treatment.DOI: http://dx.doi.org/10.3329/bmjk.v44i1-2.10473Bang Med J (Khulna) 2011: 44(1&2) 25-27